Pendampingan Usaha Packaging Mie Telor Nusantara - Adriana Madya Marampa; Neneng Sofiyanti; Dina Ramba (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This community service was carried out at one of the MSMEs in Tama Toraja. This MSME operates in the food sector. The food business in question is Mie Basah. This wet noodle is called Mie Telor Nusantara. The problem faced by MSMEs is declining sales due to the large number of competitors. Development aims to increase sales. The result of this trial is that sales of Mie Telor Nusantara increase every month.